PEMBERDAYAAN SISWA-SISWI DALAM PEMANFATAAN TANAMAN OBAT DI LINGKUNGAN DI LINGKUNGAN SEKOLAH - Dani Sujana; Yogi Rahman Nugraha; Dadang Muhammad Hasyim (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
Medicinal plants are very beneficial for health, thus reducing the impact of using drugs pharmacologically. Increasing public awareness to reduce and stop using chemical drugs encourages people to use natural ingredients that are around. The purpose of this community service is to provide education to students to utilize their yards in growing medicinal plants at home. The method used is: counseling and empowerment in planting medicinal plants in school yards. From this community service activity, it can be concluded that 95% of students who attended and took part in community service activities could understand the presentation of the substance given by the presenters, namely the D3 Pharmacy Lecturer team. Second, after the presentation of the material, knowledge about "The Benefits of Medicinal Plants in the Family Environment and Land Use in the Elementary School Environment" increased. Third, the enthusiasm of SD Al Khoiriyah IV Garut students when asking questions was very good, showing that this substance was interesting enough to be discussed.